Oxygen Reduction on Cu1.4mn1.6o4 Spinel Particles Composite Electrodes Effect of Particles Size - Ortiz-Farias, J; Ortiz-Farias, J; Gautier-Zamora, J; Gautier-Zamora, J; Rios-Vilches, E; Rios-Vilches, E; Herrera-Diaz, F; Herrera-Diaz, F; Alburquenque-Munoz, D; Alburquenque-Munoz, D (Sociedad Chilena de Quimica, 2014)
The oxygen reduction reaction (orr) was studied on CG/PPy/PPy(Ox)/PPy and CG/paint/CC(Ox)PPy composite electrodes, CG representing conducting glass, PPy polypyrrole, CC carbon cloth and Ox mixed valence spinel oxide particles of transition metals Cu1.4Mn1.6O4 in 0.2 M KCl pH = 9.2, at room temperature. PPy is electrochemically polymerized and serves as a protective layer to dispersed oxide particles in the carbon cloth. Oxide particles size varied from 7.6 to 11.2 ?m. The orr takes place on the oxide particles with formation of hydrogen peroxide which diffuses to electrolyte solution. The amount of peroxide ions produced was detected using the rotating ring-disk electrode technique and determined indirectly by iodine spectroscopy. The peroxide ions production depends strongly on the oxide particle size. © 2014, Sociedad Chilena de Quimica. All rights reserved.